The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1101/gad.1444206
|View full text |Cite
|
Sign up to set email alerts
|

A 5′ RNA element promotes dengue virus RNA synthesis on a circular genome

Abstract: The mechanisms of RNA replication of plus-strand RNA viruses are still unclear. Here, we identified the first promoter element for RNA synthesis described in a flavivirus. Using dengue virus as a model, we found that the viral RdRp discriminates the viral RNA by specific recognition of a 5 element named SLA. We demonstrated that RNA-RNA interactions between 5 and 3 end sequences of the viral genome enhance dengue virus RNA synthesis only in the presence of an intact SLA. We propose a novel mechanism for minus-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
435
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(448 citation statements)
references
References 41 publications
11
435
1
1
Order By: Relevance
“…It is located at the leading end of the first stem situated at the base of the predicted SLA structure at the 5′-end of the genome. The SLA is recognized by viral RNA polymerase (NS5) and participates in cyclization of the viral genome through the interaction with the 3′-end sequence, thereby promoting minus-strand viral RNA synthesis (Filomatori et al, 2006). Using the singleround FL-DENV/GFP RNA-launched system, we confirmed that the 5′-69M construct resulted in significantly less (P < 0.05) intracellular viral RNA levels than the FL-DENV/GFP containing wt 5′NCR construct (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…It is located at the leading end of the first stem situated at the base of the predicted SLA structure at the 5′-end of the genome. The SLA is recognized by viral RNA polymerase (NS5) and participates in cyclization of the viral genome through the interaction with the 3′-end sequence, thereby promoting minus-strand viral RNA synthesis (Filomatori et al, 2006). Using the singleround FL-DENV/GFP RNA-launched system, we confirmed that the 5′-69M construct resulted in significantly less (P < 0.05) intracellular viral RNA levels than the FL-DENV/GFP containing wt 5′NCR construct (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…The 5Ј-UTRs of flavivirus RNAs are ϳ100 nt in length and fold to form stable secondary structures (16,26,27). The 5Ј-terminal region within ϳ160 nt forms two stem-loop (SL) structures, SLA and SLB (Fig.…”
Section: The Dengue Virus (Denv)mentioning
confidence: 99%
“…NS5 has methyltransferase and RNAdependent RNA polymerase activities, whilst NS3 is a serine protease, NTPase/RNA helicase and 59 RNA triphosphatase (for a review, see Lindenbach & Rice, 2001;Luo et al, 2008). Consistent with their putative role in viral replication, both NS3 and NS5 exist as a complex in DENV-infected cells (Kapoor et al, 1995) and interact with the 39-and 59UTR of Japanese encephalitis virus and DENV RNA, respectively (Chen et al, 1997;Filomatori et al, 2006;Lodeiro et al, 2009;Luo et al, 2008). Additionally, some sequences present in the 39-and 59UTR are able to interact with cellular proteins such as La, polypyrimidine tract-binding protein (PTB), translation elongation factor 1a, Y box-binding protein 1, heterogeneous nuclear ribonucleoproteins (hnRNPs) A1, A2/B2 and Q, protein disulfide isomerase, poly(A)-binding protein (PABP) and calreticulin (De Nova-Ocampo et al, 2002;García-Montalvo et al, 2004;Paranjape & Harris, 2007;Polacek et al, 2009;Yocupicio-Monroy et al, 2003.…”
Section: Introductionmentioning
confidence: 99%